2021
DOI: 10.1002/chem.202100141
|View full text |Cite
|
Sign up to set email alerts
|

Ready Access to Anhydrous Anionic Lanthanide Acetates by Using Imidazolium Acetate Ionic Liquids as the Reaction Medium

Abstract: Access to lanthanide acetate coordination compounds is challenged by the tendency of lanthanides to coordinate water and the plethora of acetate coordination modes. A straightforward, reproducible synthetic procedure by treating lanthanide chloride hydrates with defined ratios of the ionic liquid (IL) 1-ethyl-3-methylimidazolium acetate ([C 2 mim][OAc]) has been developed. This reaction pathway leads to two isostructural crystalline anhydrous coordination complexes, the polymeric [C 2 mim] n [{Ln 2 (OAc) 7 } n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In 1 – 7 the polymeric chains are rather compact, which is characterized by two factors, the total number of bridging acetates and the high proportion of the η 3 μ 2 κ 2 mode, affecting Ln–Ln intrachain distances. In this respect 1 – 5 and 7 have strong analogies with the recently discovered series [C 2 mim]­[Ln 2 (OAc) 7 ] . The latter formally deviates from the 3:1 OAc – :Ln ratio, but one of the acetate groups is nonbridging, in fact substituting for the respective position of the N-/O-donor in 1 – 5 .…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…In 1 – 7 the polymeric chains are rather compact, which is characterized by two factors, the total number of bridging acetates and the high proportion of the η 3 μ 2 κ 2 mode, affecting Ln–Ln intrachain distances. In this respect 1 – 5 and 7 have strong analogies with the recently discovered series [C 2 mim]­[Ln 2 (OAc) 7 ] . The latter formally deviates from the 3:1 OAc – :Ln ratio, but one of the acetate groups is nonbridging, in fact substituting for the respective position of the N-/O-donor in 1 – 5 .…”
Section: Resultsmentioning
confidence: 68%
“…We have hypothesized that by dissolving f-element salts in ILs containing only soft donors (e.g., imidazoles) one could drive off volatiles, including water and carboxylic or mineral acids, leaving no choice but to complex the softer donors of the ILs . We have previously shown that f-element salt hydrates can be dissolved and dehydrated in the ILs with a common anion (e.g., nitrate or acetate). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations